2018
DOI: 10.1002/2017gl076834
|View full text |Cite
|
Sign up to set email alerts
|

Urban Modification of Convection and Rainfall in Complex Terrain

Abstract: Despite a globally growing proportion of cities located in regions of complex terrain, interactions between urbanization and complex terrain and their meteorological impacts are not well understood. We utilize numerical model simulations and satellite data products to investigate such impacts over San Miguel de Tucumán, Argentina. Numerical modeling experiments show urbanization results in 20–30% less precipitation downwind of the city and an eastward shift in precipitation upwind. Our experiments show that ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…Other factors like urban size and structure (Kingfield et al, 2018;, different climate zones, or entangling factors can furthermore lead to changes in heavier rainfall regimes. Studies, for example, evaluated urban modification of storms by coastal cities (Comarazamy et al, 2010;Hosannah & Gonzalez, 2014;Shepherd et al, 2010), cities located near artificial reservoirs (e.g., Haberlie et al, 2016), or in deserts (Diem & Brown, 2003;Diem & Mote, 2005), and recently, Freitag et al (2018) cities with complex terrains. Lowry (1998) criticizes that many assumptions of rainfall modification are based on two research campaigns in the second half of the last century.…”
Section: 1029/2018jd028858mentioning
confidence: 99%
“…Other factors like urban size and structure (Kingfield et al, 2018;, different climate zones, or entangling factors can furthermore lead to changes in heavier rainfall regimes. Studies, for example, evaluated urban modification of storms by coastal cities (Comarazamy et al, 2010;Hosannah & Gonzalez, 2014;Shepherd et al, 2010), cities located near artificial reservoirs (e.g., Haberlie et al, 2016), or in deserts (Diem & Brown, 2003;Diem & Mote, 2005), and recently, Freitag et al (2018) cities with complex terrains. Lowry (1998) criticizes that many assumptions of rainfall modification are based on two research campaigns in the second half of the last century.…”
Section: 1029/2018jd028858mentioning
confidence: 99%
“…Shepherd () proposed that interactions between orographic processes and urban‐induced circulation can produce frequent convergence at the urban interface. Freitag et al () showed that urbanization modifies terrain‐forced convection through dynamic and thermodynamic perturbations to persistent atmospheric forcings. Also, previous studies highlight the importance of considering flow regimes in urban rainfall modification studies (e.g., McLeod et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Freitag et al . () have used WRF and satellite data products to investigate such impacts over San Miguel de Tucumán, Argentina and found that urbanization results in 20–30% less precipitation downwind of the city and that it causes an eastward shift of precipitation upwind.…”
Section: Introductionmentioning
confidence: 99%